METODOLOGI PENDIDIKAN AL-IBRAH DALAM AL-QUR’AN: Kajian Historis-Paedagogis terhadap Kisah Nabi Ibrahim dalam Surat Maryam ayat 42-48 - Ismail Ansari (Jurnal Ilmiah Didaktika, 2011)
Ibrah is a condition in which someone reach an abstract knowledge from a concrete onethrough observation and contemplation to know the core of certain problem by observing, testifying, considering, measuring and deciding logically until having the conclusion that can affect someone’s heart to obey Allah. In Al Quran, there are various instances of Ibrah depend on the object of ibrah itself such as in the form of story, story of Allah’s creatures, story of His grace, and also in the form of historical events. One of ibrah that is found in Al Quran is a dialogue between Prophet Ibrahim and his father in Surah Maryam verse 42-48.